CT-guided lung biopsy: diagnostic accuracy and complication rates of biopsy techniques - Deniz, Muhammed Akif; Cakir, Caglayan; Kilinc, Fatth; Kurt, Osman; Tas Deniz, Zelal (Marmara Univ, Fac Medicine, 2022)
Objective: We aimed to evaluate the diagnostic accuracy and complication rates of computed tomography (CT)-guided core needle biopsy and fine needle aspiration biopsy (FNAB). Materials and Methods: Patients who underwent CT-guided lung mass biopsy were included. The patients were evaluated in terms of age, gender, lesion diameter, lesion localization, depth of the mass, type of biopsy procedure (core needle biopsies and FNAB). Results: The accuracy rate of FNAB in diagnostic material was found to be 100% in terms of benign, malignant and all lesions. The specificity and sensitivity of FNAB was found to be 100%. The diagnostic accuracy rate of core needle biopsy was found to be 70% in benign lesions, 100% in malignant lesions. The specificity of core needle biopsy was 90% and sensitivity 100%. There was no statistically significant difference between the two biopsy techniques in terms of complications. Conclusion: In conclusion, we found that the diagnostic rates of FNAB and core needle biopsy were close in malignant lesions, the diagnostic rate of core needle biopsy was higher in benign lesions, and there was no difference in terms of complications in both biopsy techniques.
Keywords: Lung; Mass; Transthoracic biopsy; Computed tomography